Systems and processes of knowledge organization: A conceptual analysis of the Brazilian information science literature - Moreira, Walter [UNESP]; Pegoraro Novaes, Fernanda Carolina [UNESP]; Santana De Moraes, Isabela [UNESP] (My University, 2019)
In the terminology interface between Library and Information Science and Knowledge Organization, some terms have gained prominence without their scopes being however sufficiently clear. Considering this framework, we established as objectives to map and systematize the use of the terms knowledge organization systems (KOS) and knowledge organization processes (KOP) in Brazilian journals of Library and Information Science. To do so, we used the methodology of content analysis and used as corpus a set of papers published in Brazilian journals classified with “Qualis/Periódicos” “A1” or “A2” that discusses the terms KOS and KOP. The concepts under analysis were discussed based on the following categories defined a posteriori: comparison with other instruments, typologies, theoretical bases, and applications and uses. It was verified that there is still no consensus on the scope of the concept KOS; and that the expression KOP is not yet widely used in the Brazilian literature. The typologies are not yet formally stated. Thesaurus, classification systems, and ontologies are indicated as more common types of KOS, and as common types of KOP classification and indexing, all oriented towards information organization, representation, and retrieval. As a challenge for future works, we think it's possible to enrich the conceptual analysis by the application of onomasiology axis.
Sistemas e processos de organização do conhecimento: Uma análise conceitual da literatura Brasileira de ciencia da informação
Keywords: Brasil; Knowledge organization; Knowledge organization processes; Knowledge organization systems